Frequency and clinical features of Lewy Body Dementia in ItalianMemory Clinics - Farina, E.; Baglio, F.; Caffarra, et al., P. (Acta Biomedica Atenei Parmensis, 2009)
Background: The latest developments in Lewy Body Dementia (DLB) raise some controversies on clinical features, neuroimaging and therapy. The aim of our study is to determine clinical, neuropsychological, neuroimaging and EEG profile of DLB through retrospective and prospective data of 102 patients. Methods: data were collected with an analytical form that was developed by an expertise of neurologists. Results: DLB represented 4.8% of the dementia population, with no sex difference. Family history of dementia was common (24.5%), while familiarity for parkinsonism was rare (4.9%). Cognitive disturbances were the predominant clinical presentation at onset (49%), followed by behavioral symptoms (29.4%) and parkinsonism (21.6%). Clinical features at consultation were: memory disturbances (almost all cases), symmetrical (68.6%) or asymmetrical (18.6%) parkinsonism, cognitive fluctuations (49%), visuospatial deficits (53.9%), and visual hallucinations (44.1%). Autonomic signs were present in a third of the cases, while sleep disorders were present in 44.1%. Some clinical response to antiparkinsonian drugs was evident in half of the cases. MRI, SPET, EEG and Neuropsychiatric Inventory data were available in a subgroup of patients. Conclusions: Most of our data were in accordance with the previous literature. However, some data underline the relationship between DLB, Alzheimer’s and Parkinson’s disease.